2018
DOI: 10.11648/j.ijnfs.20180703.13
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine and Quinine Differently Inhibit the Early Phase of Acetylcholine-Dependent Contraction of Mouse Ileum <i>in vitro</i>

Abstract: Thiamine and quinine are popular bitter substances and their physiological effects have been studied; however, their impact on digestion remains unknown. Here, the physiological effects of thiamine and quinine was investigated for in vitro contraction of mouse ileum. Acetylcholine stimulates autonomous contraction of mouse ileum in a dose-dependent manner. The effect of Acetylcholine for contraction of ileum was partly suppressed by the adrenaline administration. Upon simultaneous treatment of the ileum by ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…3A). Similar results have been recently published for quinine (10), where 100 μM of quinine had no effect on PMA but reduced the tonic contractions evoked by 100 ng/ml of Ach. Based on the poor affection of PMA and a signifi cant reduction in the contraction intensity, as well as on the fi ndings of previous studies suggesting the involvement of serotoninergic receptors and enterochromaffi n cells in the mechanism of action of quinine (16), the authors indicated a possible involvement of some different mechanism other than the one directly involving the myenteric plexus (10).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…3A). Similar results have been recently published for quinine (10), where 100 μM of quinine had no effect on PMA but reduced the tonic contractions evoked by 100 ng/ml of Ach. Based on the poor affection of PMA and a signifi cant reduction in the contraction intensity, as well as on the fi ndings of previous studies suggesting the involvement of serotoninergic receptors and enterochromaffi n cells in the mechanism of action of quinine (16), the authors indicated a possible involvement of some different mechanism other than the one directly involving the myenteric plexus (10).…”
Section: Resultssupporting
confidence: 90%
“…3B). The measured PMA indicates whether the contraction of ileum tissue is mediated through the myenteric plexus or indirectly through the diffuse intestinal neuroendocrine system (10). Although PMA after Ach application remained unaffected by Cin (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For the preparation of in vitro studies, a 1-cm-long portion of the murine jejunum and ileum were isolated while keeping mice under barbiturate anesthesia (Nembutal, 20 mg/kg, intraperitoneal injection). Then, the inner contents of the isolated jejunum and ileum were washed for three time with prewarmed Tyrode's solution (37°C) and, subsequently, the isolated tissue fragment of the jejunum or ileum was fixed in a Magnus-type chamber filled with O 2 -saturated Tyrode's solution (37°C), as described previously [24]. Next, the proximal end of the preparation was set upward and connected to a strain gage through a cotton thread (Daruma#30; Yokoi, Osaka, Japan).…”
Section: Movement Analysis Of the Jejunummentioning
confidence: 99%
“…In addition, caffeine inhibits nonselective cationic currents in ICCs from the murine jejunum and relaxes the smooth muscle through the actin depolymerization [22,23]. Recently, it was reported that thiamin, which is known to binds to a bitter taste receptor, modifies the early phase of the ileum contraction [24], whereas the physiological effects of thiamin on the rhythm and amplitude of jejunum and ileum contractions remain unclear. Thus, this study aimed to elucidate the physiological effects of thiamin compared with quinine in the contraction of the murine jejunum and ileum.…”
Section: Introductionmentioning
confidence: 99%